Técnica, ciência e neutralidade no pensamento de Herbert Marcuse - Pisani, Marilia Mello (2008)
Herbert Marcuse was the author of a controversial critique of the thesis of the neutrality of technology and science, presented mainly in his book published in 1964, One-Dimensional Man: studies in the ideology of advanced industrial society. The aim of the work is an understanding of that critique, and it is divided into three parts. The first one deals with the influence that the philosophical discussions of the 1940 s and 1950 s had on the development of the theme in Marcuse s thought. The second part is a study of the origins of the critique of neutrality in texts written by Marcuse in his youth that brings to light the very peculiar way he articulates philosophy and Marxism, which in turn, as it is shown in the third part, leads to a severe criticism of the advanced industrial societies. The approach to technique, science and politics that follows from that double philosophic and social conception is the basis for the structuring of Marcuse s thought.